Soubriquet nomination as referred to cultural awareness and intercultural competence - Elizaveta A. Vishnyakova; Olga D. Vishnyakova (Peoples' Friendship University of Russia (RUDN University), 2020)
The article deals with the analysis of the English soubriquet nomination in terms of its linguo-cultural potential realisation in reference to cultural awareness and intercultural competence development in language education process. Soubriquets can be used to pass cultural information and knowledge represented in language and speech. On the basis of complex methodology that integrates linguistic and linguo-cultural approaches to soubriquets within the English-speaking communities, nicknames are considered as part of cultural historical continuum, including their variation properties. The analysis of media materials serves to penetrate into the sphere of linguo-cultural peculiarities of soubriquet nominations used in political discourse to persuade and manipulate target audience by means of memes encoded by the linguistic units in question, presented in discourse to pass evaluative and cultural information within new discursive formats, reflecting current trends in the communicative processes. The use of soubriquets in literary works implies the reader's cultural awareness that facilitates recognition and understanding of cultural contexts, which becomes important for intercultural competence development as it reflects typical characteristics of a given culture realised in language manifestations.